Neuropalliative care: Priorities to move the field forward. (31st July 2018) - Creutzfeldt, Claire J.; Kluger, Benzi; Kelly, Adam G.; Lemmon, Monica; Hwang, David Y.; Galifianakis, Nicholas B.; Carver, Alan; Katz, Maya; Curtis, J. Randall; Holloway, Robert G.
Abstract : Neuropalliative care is an emerging subspecialty in neurology and palliative care. On April 26, 2017, we convened a Neuropalliative Care Summit with national and international experts in the field to develop a clinical, educational, and research agenda to move the field forward. Clinical priorities included the need to develop and implement effective models to integrate palliative care into neurology and to develop and implement informative quality measures to evaluate and compare palliative approaches. Educational priorities included the need to improve the messaging of palliative care and to create standards for palliative care education for neurologists and neurology education for palliative specialists. Research priorities included the need to improve the evidence base across the entire research spectrum from early-stage interventional research to implementation science. Highest priority areas include focusing on outcomes important to patients and families, developing serious conversation triggers, and developing novel approaches to patient and family engagement, including improvements to decision quality. As we continue to make remarkable advances in the prevention, diagnosis, and treatment of neurologic illness, neurologists will face an increasing need to guide and support patients and families through complex choices involving immense uncertainty and intensely important outcomes of mind and body. This article outlines opportunities to improve the quality of care for all patients with neurologic illness and their families through a broad range of clinical, educational, and investigative efforts that include complex symptom management, communication skills, and models of care.